2000
DOI: 10.1016/s0167-4889(00)00033-1
|View full text |Cite
|
Sign up to set email alerts
|

Novel effects of gossypol, a chemical contraceptive in man: mobilization of internal Ca2+ and activation of external Ca2+ entry in intact cells

Abstract: The effect of gossypol on Ca(2+) signaling in Madin Darby canine kidney (MDCK) cells was investigated by using fura-2 as a Ca(2+) probe. Gossypol evoked a rise in cytosolic free Ca(2+) levels ([Ca(2+)](i)) concentration-dependently between 2 and 20 microM. The response was decreased by external Ca(2+) removal. In Ca(2+)-free medium pretreatment with gossypol nearly abolished the [Ca(2+)](i) increase induced by carbonylcyanide m-chlorophenylhydrazone (CCCP), a mitochondrial uncoupler, and thapsigargin, an inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…In addition to being identified as a BH3-mimetic by computer-assisted molecular modeling, nuclear magnetic resonance imaging, and fluorescence-polarization assays, other studies have demonstrated that gossypol can inhibit DNA synthesis [19], cellular energy metabolism [55], [56], protein kinase C [21], telomerase [57] and the human mitotic kinesin, EG5 [58]. In addition to these actions, gossypol can modulate calcium homeostasis [20] and TGF-β1 signaling [59]. In the wake of the structural studies indicating that gossypol is a BH3-mimetic, it was found that gossypol can activate the intrinsic apoptotic pathway by increasing reactive oxygen species [60], activating p53 [61] and suppressing NF-κB activity [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to being identified as a BH3-mimetic by computer-assisted molecular modeling, nuclear magnetic resonance imaging, and fluorescence-polarization assays, other studies have demonstrated that gossypol can inhibit DNA synthesis [19], cellular energy metabolism [55], [56], protein kinase C [21], telomerase [57] and the human mitotic kinesin, EG5 [58]. In addition to these actions, gossypol can modulate calcium homeostasis [20] and TGF-β1 signaling [59]. In the wake of the structural studies indicating that gossypol is a BH3-mimetic, it was found that gossypol can activate the intrinsic apoptotic pathway by increasing reactive oxygen species [60], activating p53 [61] and suppressing NF-κB activity [62].…”
Section: Discussionmentioning
confidence: 99%
“…The anti-fertility action of gossypol was thought to be due to inhibition of the cellular energy metabolism of spermatogonia [18] rather than its action as a BH3-mimetic. Several other modes of cytotoxic action have also been attributed to gossypol including inhibition of DNA synthesis and cell cycle arrest [19], altered intracellular calcium regulation [20], inhibition of protein kinase C [21], interaction with steroid receptor co-activators [22] and modulation of several components of mitochondrial apoptotic signaling [23]. There is also recent evidence that gossypol can induce autophagy, which in some cases leads to autophagic cell death [24].…”
Section: Introductionmentioning
confidence: 99%
“…Because the activation of ER stress following treatment occurs rapidly (Ͻ2 h), whatever stress links gossypol to this response must also occur rapidly. Several reports have demonstrated that gossypol causes a rapid increase in cytoplasmic calcium as a consequence of release of calcium from ER stores, and subsequent influx through calcium release-activated channels (33)(34)(35). In addition, the release of calcium from ER stores and increases in cytoplasmic calcium are known activators of the ER stress response (36).…”
Section: Noxa Is Required For Gossypol-mediated Sensitization Tomentioning
confidence: 99%
“…Gossypol Rapidly Increases Phospholipase A2 Activity, Leading to Increased Cytoplasmic Calcium, ER Stress, and NOXA Induction-A previous report demonstrated that aristolochic acid, an inhibitor of PLA2, prevented the increase in cytoplasmic calcium induced by gossypol, but whether gossypol actually increases PLA2 activity was not assessed (33). Moreover, many reports have demonstrated multiple levels of cross-talk between PLA2 and calcium, and in the majority of cases, an increase in cytoplasmic calcium is required for the increase in PLA2 activity (37).…”
Section: Noxa Is Required For Gossypol-mediated Sensitization Tomentioning
confidence: 99%
“…37, 38 Similarly to BH3I-2′ and HA14-1, in the absence of extracellular Ca 2+ , bax −/− cells did not respond to gossypol (Figure 6a, black trace). In WT cells in the presence of external Ca 2+ , 20  μ M gossypol alone caused an increase in [Ca 2+ ] i reaching a sustained elevated plateau (Figure 6a).…”
Section: Resultsmentioning
confidence: 93%